IMMIGRANT POPULATION IN BARCELONA: RESIDENTIAL CHARACTERISTICS AND USE OF PUBLIC SPACE - Blanca Gutiérrez Valdivia; Adriana Ciocoletto; Pilar García Almirall; Zaida Muxí Martínez (European Regional Science Association (ERSA), 2010)
The arrival of numerous immigrant populations in the last decade is causing deep changes in the physical and social morphology of the Spanish cities. This population locates in specific areas of our cities and has distinct settlement patterns from those of the native population. Likewise, the characteristics of their housing and the use that they make of the public space are different from those of the rest of the population. In this paper does a characterization of the physical conditions of the dwellings where this population live and of the public space that the immigrants use and the social consequences that these challenges involve. The territorial area of the research is the Metropolitan Region of Barcelona. It has been developed in different neighborhoods of the RMB with different urban and demographic characteristics and with a high concentration of immigrant population. The methodology used has been a combination of quantitative and qualitative techniques. First of all, a quantitative approach on the housing and the public space of the zone of studied has been made. Afterwards, different qualitative methods to study the results in depth (participant observation, interviews, analysis of photographies) have been used.
Keywords: 330; immigrant population; housing; public space; qualitative